Intercultural Transfer and Balinese Gamelan Preservation - Emma Lo (UNHI PRESS, 2020)
The influence and spread of traditional Balinese music over time and across regions has been conducted through a number of different channels. In addition to locally-focused efforts, cultural transfer has also contributed to the preservation of traditional Balinese arts. From the self-interested, strategic support of gamelan music by Japanese occupational forces to the global experimental music scene today, Balinese arts have been shared, supported, translated, and appropriated in various ways by a number of different actors to political, artistic, and commercial ends. Building on Michel Espagneâ€™s definition of cultural transfer and Stephen Greenblattâ€™s concept of cultural mobility, this paper aims to outline different modes of cultural transfer (or â€œbridges,â€ as Espagne would say), with explicit attention to power dynamics and multi-way flows of influence. Several key historical and contemporary examples of the transfer of traditional Balinese music will be discussed in an effort to better understand the relationship between cultural transfer and preservation.